The impeachers : the of trial of Andrew Johnson and the dream of a just nation - Wineapple, Brenda (Random House, 2019)
"When Lincoln was assassinated and Andrew Johnson became President, a fraught time in America became perilous. Congress was divided over how Reconstruction should be accomplished and the question of black suffrage. The South roiled with violence, lawlessness, and efforts to preserve the pre-Civil War society. Andrew Johnson--chosen as Vice President for electability, because he was a Southern Democrat--had no interest in following Lincoln's agenda. With the unchecked power of executive orders, Johnson pardoned the rebel states and their leaders, opposed black suffrage, and called Reconstruction unnecessary. Congress decided to take action against a President who acted like a king. With extensive research and profound insights, Brenda Wineapple makes this overlooked historical period come alive with important new insights. The impeachment--the first in American history--was the last-ditch, patriotic effort make the goals of the Civil War a reality, and to make the Union one again"--